Strategi Pemulihan Akuntabilitas Kinerja Melalui Optimalisasi Arsitektur Perencanaan Kabupaten Lombok Utara - Eka Yuli Kurniawati (Bajang Institute, 2026)
The SAKIP of North Lombok Regency has experienced a declining trend in cumulative scores during the 2022–2025 period, primarily due to deteriorating performance in the planning component. The Regional Head’s Priority Programs outlined in the 2025–2029 RPJMD have not yet been successfully translated into the Strategic Plans (Renstra) of Regional Government Agencies due to limited timelines, insufficient understanding of SMART indicators, sectoral egos, and the automatic locking mechanism of the SIPD-RI application. The Cost-Benefit Analysis (CBA) method was selected to address these challenges. This policy paper recommends strengthening collective capacity through a SMART-Cascading Performance Clinic and establishing a Cross-Cutting Task Force. This integrated policy is considered the most tactical, efficient, and systemically impactful approach to resolving upstream conceptual bottlenecks, dismantling silo-based work cultures, and continuously improving the competencies of planning officials, thereby restoring and improving the regional SAKIP performance score.